Efektivitas Sistem Keuangan Desa dalam Meningkatkan Kinerja Keuangan Desa Mantigola - husriah ria (Prodi Akuntansi FEB UNITOMO, 2022)
This study aims to determine the effectiveness of the village financial system in improving the financial performance of Mantigola Village. This type of research uses a qualitative descriptive method. The sampling technique is observation, interviews and documentation. The data was processed using a qualitative descriptive method. The results of the research on the Village Financial System Application (Siskeudes) have been successfully implemented in Mantigola Village, measured from the availability of human resources and the existing facilities and infrastructure in Mantigola Village are adequate to apply this application. The application of the Village Financial System (Siskeudes) application in Mantigola village has been said to be successful, because in its application the Village Financial System application (Siskeudes) in Mantigola village has helped the Mantigola village government in improving village financial management to be more efficient and also the application of the Financial System The village (Siskeudes) can improve the transparency of the Mantigola village government in managing village finances for the better.